Enhancing upper-limb neurorehabilitation in chronic stroke survivors using combined action observation and motor imagery therapy - Binks, Jack Aaron; Emerson, Jonathan Reyes; Scott, Matthew William; Wilson, Christopher; van Schaik, Paul; Eaves, Daniel Lloyd (Frontiers in Neurology, 2023)
Introduction For people who have had a stroke, recovering upper-limb function is a barrier to independence. When movement is difficult, mental practice can be used to complement physical therapy. In this within-participants study we investigated the effects of combined action observation and motor imagery (AO + MI) therapy on upper-limb recovery in chronic stroke survivors. Methods A Graeco-Latin Square design was used to counterbalance four mental practice conditions (AO + MI, AO, MI, Control) across four cup-stacking tasks of increasing complexity. Once a week, for five consecutive weeks, participants (n = 10) performed 16 mental practice trials under each condition. Each trial displayed a 1st person perspective of a cup-stacking task performed by an experienced model. For AO, participants watched each video and responded to an occasional color cue. For MI, participants imagined the effort and sensation of performing the action; cued by a series of still-images. For combined AO + MI, participants observed a video of the action while they simultaneously imagined performing the same action in real-time. At three time points (baseline; post-test; two-week retention test) participants physically executed the three mentally practiced cup-stacking tasks, plus a fourth unpractised sequence (Control), as quickly and accurately as possible. Results Mean movement execution times were significantly reduced overall in the post-test and the retention test compared to baseline. At retention, movement execution times were significantly shorter for combined AO + MI compared to both MI and the Control. Individual participants reported clinically important changes in quality of life (Stroke Impact Scale) and positive qualitative experiences of AO + MI (social validation). Discussion These results indicate that when physical practice is unsuitable, combined AO + MI therapy could offer an effective adjunct for neurorehabilitation in chronic stroke survivors.